The Ecocultural Context and Child Behavior Problems: A Qualitative Analysis in Rural Nepal - Burkey, Matthew D. (Soc Sci Med, 2016)
Commonly used paradigms for studying child psychopathology emphasize individual-level factors and often neglect the role of context in shaping risk and protective factors among children, families, and communities. To address this gap, we evaluated influences of ecocultural contextual factors on definitions, development of, and responses to child behavior problems and examined how contextual knowledge can inform culturally responsive interventions. We drew on Super and Harkness’ “developmental niche” framework to evaluate the influences of physical and social settings, childcare customs and practices, and parental ethnotheories on the definitions, development of, and responses to child behavior problems in a community in rural Nepal. Data were collected between February and October 2014 through in-depth interviews with a purposive sampling strategy targeting parents (N=10), teachers (N=6), and community leaders (N=8) familiar with child-rearing. Results were supplemented by focus group discussions with children (N=9) and teachers (N=8), pile-sort interviews with mothers (N=8) of school-aged children, and direct observations in homes, schools, and community spaces. Behavior problems were largely defined in light of parents’ socialization goals and role expectations for children. Certain physical settings and times were seen to carry greater risk for problematic behavior when children were unsupervised. Parents and other adults attempted to mitigate behavior problems by supervising them and their social interactions, providing for their physical needs, educating them, and through a shared verbal reminding strategy (samjhaune). The findings of our study illustrate the transactional nature of behavior problem development that involves context-specific goals, roles, and concerns that are likely to affect adults’ interpretations and responses to children’s behavior. Ultimately, employing a developmental niche framework will elucidate setting-specific risk and protective factors for culturally compelling intervention strategies.